2016
DOI: 10.1016/j.joca.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of meniscus extrusion predict incident radiographic knee osteoarthritis – data from the Osteoarthritis Initiative

Abstract: SUMMARY Objective To test the hypothesis that quantitative measures of meniscus extrusion predict incident radiographic knee osteoarthritis (KOA), prior to the advent of radiographic disease. Methods 206 knees with incident radiographic KOA (Kellgren Lawrence Grade (KLG) 0 or 1 at baseline, developing KLG 2 or greater with a definite osteophyte and joint space narrowing (JSN) grade ≥1 by year 4) were matched to 232 control knees not developing incident KOA. Manual segmentation of the central five slices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 29 publications
5
91
0
Order By: Relevance
“…Several recent studies described a new approach for quantitative MRI analysis of meniscal extrusion using 3D imaging techniques 9,10 , which might be a more reliable way to assess volumetric morphometry and extrusion of the meniscus and a more truthful representation of the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies described a new approach for quantitative MRI analysis of meniscal extrusion using 3D imaging techniques 9,10 , which might be a more reliable way to assess volumetric morphometry and extrusion of the meniscus and a more truthful representation of the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…The generally accepted idea is that a displaced meniscus affects the weight-bearing and load distribution capacities within the knee joint, which leads to loss of cartilage and increase in bone marrow lesions, ultimately resulting in knee OA [6][7][8] . Multiple studies affirm this relationship between meniscal extrusion and the development of knee OA or features thereof [6][7][8][9][10] . However, most of these studies were carried out in cohorts of subjects with established OA.…”
Section: Introductionmentioning
confidence: 92%
“…Cartilage thickness and meniscal volume and locations are morphological parameters sensitive to changes in early-OA and, consequently, were analyzed in this study. 6,27 Average cartilage thickness over the total area of subchondral bone on the tibial plateau in the medial femorotibial compartment was measured using a manual, quality-controlled segmentation using custom software (Chondrometrics, Ainring, Germany). Meniscus volume measurements in the posterior horn of the medial meniscus were performed manually using Amira FEI (Hillsboro, OR).…”
Section: Morphometrymentioning
confidence: 99%
“…Most recently, Driban et al examined a cohort from the OAI database and note accelerated knee OA in patients with MRI findings of medial meniscus pathology with extrusion and others with subchondral damage at baseline [25]. Similarly, OAI data showed that medial meniscus extrusion predicts a higher rate of incident radiographic knee OA, and that extrusion was more pronounced in those with earlier incident OA [26]. …”
Section: Discussionmentioning
confidence: 99%